Analisis Faktor-Faktor yang Mempengaruhi Konsumen dalam Keputusan Pembelian Paket Data Telkomsel - Lestari, Titi Dwi (Indonesian Journal of Strategic Management, 2021)
This research intends to analyze the impact of product quality, price, promotion, and brand image on user decisions in purchasing Telkomsel data packages. The research method uses associative quantitative methods. The research sample used is non-probability sampling with a total of 102 Telkomsel data package users in the Soloraya area as respondents. Collecting data using a questionnaire method and the primary data required using quantitative analysis methods. Data analysis was carried out using multiple linear regression analysis. The research shows that the calculation of the coefficient of determination (RÂ²) is 0.690 or 69%. The conclusion obtained from the results of hypothesis testing shows that the t value of the product quality variable is 0.415 which indicates that there is no significant effect on purchasing decisions, the t value of the price variable is 0.006 which means it has a significant and positive impact on purchasing decisions, the t value of the variable t count promotion of 0.007 which means that it has a significant and positive effect on purchasing decisions, while the t value of the brand image variable is 0.001 which means it has a positive influence on purchasing decisions of Telkomsel data packages in Soloraya.